The Relationship between Teacher Creativity in the Learning Process and Student Learning Motivation during the Covid Pandemic Period at Madrasah Ibtidaiyah: Hubungan Kreativitas Guru dalam Proses Pembelajaran Terhadap Motivasi Belajar Siswa pada Masa Pandemi Covid di Madrasah Ibtidaiyah - Putri, Novi Suparto; Istikomah, Istikomah (Indonesian Journal of Education Methods Development, 2022)
This study aims to determine the relationship between teacher creativity in the learning process and student learning motivation during the covid pandemic at MI Muhammadiyah 3 Penatarsewu. The research method used is quantitative with a correlational research design. The assessment instrument used is a statement in the form of multiple choice, totaling 10 questions to find out the answers of the respondents. The sample of this study was class 3 at MI Muhammadiyah 3 Penatarsewu with a total of 20 respondents. The sampling technique in this research is purposive sampling. Data analysis using Pearson correlation test. Data analysis using Pearson correlation test through IBM SPSS 24.0 application. The results of the research on the Pearson correlation test of teacher creativity on learning motivation show that the value of Sig. (2-tailed) of the variable of teacher creativity and student learning motivation is 0.113 which means > 0.05, then the variable of teacher creativity and student motivation is not correlated (not related). While the Pearson Correlation value is 0.366 and there is a negative value. Then the variables of teacher creativity and student learning motivation include imperfect correlations or weak correlations because the Pearson correlation value is < 1.00. If there is a negative value, it means that the higher the value of teacher creativity, the lower the value of student learning motivation and vice versa, the lower the value of teacher creativity, the higher the value of student learning motivation. It can be concluded that the teacher's creativity variable on student learning motivation has a correlation with the degree of relationship, namely the weak correlation and the form of the relationship is negative.